(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
This study intends to determine differences in students’ mathematical communication skills taught using the open-ended approach with the aid of teaching aids, expository assisted teaching aids and conventional approaches to integer operation material in class VII students. The population in this study were all students of class VII SMP Negeri 37 Medan, and three classes were selected, namely: class VII C as the experimental class 1 which was taught with an open approach assisted by teaching aids, class VII B as the experimental class. Class 2 is taught using an expository assisted approach with teaching aids and class VII A as a control class is taught conventionally. It turns out that Fcount> Ftable so that H0 is rejected, which means that there is a difference between the three samples. Because H0 was rejected, it was continued to the Tukey test. So it can be perceived that there is a significant comparison between the mathematical communication skills of students taught using the open-ended approach with the help of teaching aids, expository assisted teaching aids and conventional approaches to integer operation material for seventh grade students of SMP Negeri 37 Medan, so it is hoped that the Open-ended approach End assisted teaching aids can be used as one of the preferences to improve students’ mathematical communication skills.